Slapstick, too! [videorecording (DVD)] - Rogers, John; Lawton, Bruce; Chaplin, Charlie, 1889-1977; Laurel, Stan; Hardy, Oliver, 1892-1957; Keaton, Buster, 1895-1966; Lloyd, Harold (Shanachie, 2004)
An illuminating, fun-filled look back at early film comedy and the great masters of the art. Features the hilarious antics of Charlie Chaplin, Laurel and Hardy, Buster Keaton, Harold Lloyd, Fatty Arbuckle, the Marx Brothers, W.C. Fields and many more. These comic legends drew their characters and style from the raucous humor of the vaudeville stage where the wild anarchy of slapstick was king. Loaded with non-stop, side-splitting scenes from early films that show these greats at the peak of their powers.